Peran Orang tua dan Guru dalam Pemeliharaan Kesehatan Gigi dan Mulut di SDN Wijayakusuma 01 - Asia, Asyurati; Wijaya, Haryanto; Faudah, Meiny; Aryani, Ria; Anggraini, Wita (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Dental health is one of the important aspects in maintaining overall body health. Healthy teeth not only provide aesthetic benefits, but also play a role in the digestion and speech process. Many people still do not understand how important it is to maintain dental and oral health. A common problem in children is dental caries, which can pose a great danger to children's physical, psychological, and social health by causing dental discomfort and subsequent tooth loss, which makes eating, talking, sleeping, and socializing difficult. The role of mothers as parents and teachers at school serves as a key model for the development of children's dental and oral health behaviors. As a result, developing good basic dental and oral health behaviors is essential to establishing dental health standards that will be maintained into adulthood. The purpose of this activity is to improve the knowledge and attitudes of mothers and teachers at Wijayakusuma 01 Elementary School, Grogol Petamburan West Jakarta in maintaining and preserving children's dental and oral health through providing education accompanied by filling out pre- and post-test questionnaires. This activity was carried out by team members from the Bachelor of Dentistry study program, profession, and the Specialist Dentist Education Program of the Faculty of Dentistry, Trisakti University, in the form of counseling on Dental and Oral Health to representatives of mothers and teachers at Wijayakusuma 01 Elementary School, Grogol Petamburan sub-district, West Jakarta.